Outsiders inside : whiteness, place, and Irish women - Walter, Bronwen (Gender, racism, ethnicity., 2001)
"Outsiders Inside explores the themes of displacement and the meanings of home for these women and their descendants. This work juxtaposes the visibility of Irish women in the United States with their marginalization in Britain. Bronwen Walter challenges linear notions of migration and assimilation by demonstrating that two forms of identification can be held simultaneously. By exploring the life stories of Irish women living in Britain in the 1990s, she traces the inextricable links between gender, ethnicity and place in these diasporic identities." "In an age when the 'Celtic Tiger' economy and the Northern Ireland peace process are rapidly changing global perceptions of Irishness, this book reminds us that gender and race reamin powerful subtexts. Outsiders Inside moves the empirical study of the Irish diaspora out of the 'ghetto' of Irish Studies and into the mainstream, challenging theorists and policy-makers to pay attention to the issue of white diversity."--Jacket